Is Homework Necessary - Sridevi, K. V.; Tomar, Pooja (THE PRIMARY TEACHER, 2016)
Homework is a formative assessment mechanism, wherein, teachers, students and parents are constructively involved in the teaching–learning process. It is an integral part of classroom transaction. To find out the opinion of teachers, students and parents on homework, a questionnaire was developed by the researchers. Copies of the questionnaire were distributed among 40 parents, 40 students and 30 teacher–educators. Semi-structured interviews were conducted to add the qualitative data obtained. The findings of the study reveal that all stakeholders unanimously concur that homework is an essential component of the teaching–learning process. It was also observed that homework need not only be engaging, interesting and meaningful, involving continuous learning, but also provide a reflective practice to students.